Acquisition and processing of point clouds to support building damage assessment :Powerpoint - Khoshelham, K. (University of Twente, 2020)
This lecture presents: Why building damage assessment?; Why point clouds?; Acquisition of point clouds; Classification of damaged roofs in aerial point clouds; Classification of damaged roofs in aerial point clouds; What are features of damaged/intact roof segments?; Feature selection; Visual analysis; Structural health monitoring.